Political Agonism for Indonesian Cyberpolitic: Critical Cyberculture to Political Campaign of 2019 Indonesian Presidential Election in Twitter - Heni Gusfa; Fransiskus Emilus D. Kadjuand (Nyimak: Journal of Communication, 2020)
In this era of third-generation media, political battles not only occur in the real world but also occur in cyberspace. Various strategies and products of political campaigns using social media have become commonplace in political communication. This happens because along with the disruption of public communication media, conventional campaign ideas and models have also expanded into cyber channels and shaped cyber politics reality. The uniqueness of this research is antagonistic narratives such as hoax, ethnicity, religion, race, intergroup, and provocation in the 2019 Presidential Election political campaign on Twitter from January 1st, 2019 to April 13th, 2019. This research intends to critically analyze the narrative of political campaigns on Twitter using the Agonism Cyber-politic approach. The method used in this research is Multimodal Critical Cyberculture Analysis to analyze the multimodality text (text and image components), Using hashtags to amplificated a political narration, and the antagonism narrations that develops on Twitter by supporting accounts of Jokowi and Prabowo. The results showed that the @jokowi and @prabowo accounts were the accounts with the highest engagement in spreading political campaign narratives on Twitter. The @jokowi account uses optimistic narratives, while @prabowo tends to use pessimistic narratives. Nevertheless, there are so many antagonism narratives like hoax, fake news, propaganda, and politicization of SARA which are specified by anonymous accounts. These antagonistic narratives are more developed in cyber politics discourse on Twitter. The result is horizontal conflict among Indonesian people. The community represented by netizens experienced division and formed two clusters. This fact certainly reduces the meaning of Indonesian democracy which should be substantive to mere procedural. It was found out that the concept of agonistic politics becomes practice of Indonesian democracy, based on the philosophy of the Indonesian nation Keywords: Jokowi, Prabowo, 2019 Presidential Election, political campaign, twitter, cyber politic, Indonesian cyber-democracy ABSTRAKDi era media generasi ketiga sekarang ini, pertarungan politik tidak hanya terjadi di dunia nyata, tetapi juga terjadi di dunia maya. Berbagai strategi dan produk kampanye politik menggunakan media sosial menjadi hal yang lumrah dalam komunikasi politik. Hal ini terjadi karena seiring dengan terganggunya media komunikasi publik, ide dan model kampanye konvensional juga merambah ke saluran siber dan membentuk realitas politik siber. Keunikan dari penelitian ini adalah narasi antagonis seperti hoax, etnisitas, agama, ras, antargolongan, dan provokasi dalam kampanye politik Pilpres 2019 di Twitter dari 1 Januari hingga 13 April 2019. Penelitian ini ingin menganalisis secara kritis narasi kampanye politik di Twitter dengan pendekatan Agonism Cyber-politic. Metode yang digunakan dalam penelitian ini adalah Multimodal Critical Cyberculture Analysis, bertujuan untuk menganalisis teks multimodal (komponen teks dan gambar), penggunaan hashtag untuk memperkuat narasi politik, dan narasi antagonisme yang berkembang di Twitter dengan mendukung akun Jokowi dan Prabowo. Hasil penelitian menunjukkan bahwa akun @jokowi dan @prabowo merupakan akun yang paling banyak terlibat dalam menyebarkan narasi kampanye politik di Twitter. Akun @jokowi menggunakan narasi optimis, sedangkan @prabowo cenderung menggunakan narasi pesimistis. Namun demikian, banyak ditemukan narasi antagonisme, seperti hoax, fake news, propaganda, dan politisasi SARA yang dibocorkan oleh akun anonim. Narasi antagonis ini lebih berkembang dalam wacana politik dunia maya di Twitter. Akibatnya terjadi konflik horizontal dalam kehidupan (politik) masyarakat Indonesia. Komunitas yang diwakili oleh netizen mengalami perpecahan dan membentuk dua kluster. Fakta ini tentu mereduksi makna demokrasi Indonesia yang semestinya substantif menjadi sekadar prosedural. Konsep politik agonistik sendiri sudah menjadi bagian dari praktik demokrasi di Indonesia yang berlandaskan pada falsafah bangsa Indonesia.Kata Kunci: Jokowi, Prabowo, Pilpres 2019, kampanye politik, Twitter, politik siber, demokrasi siber Indonesia